Multifunctional PA6 composites using waste glass fiber and green metal organic framework/graphene hybrids. Issue 9 (22nd August 2022) - Unnikrishnan, Vishnu; Zabihi, Omid; Li, Quanxiang; Ahmadi, Mojtaba; Ferdowsi, Mahmoud Reza Ghandehari; Kannangara, Thathsarani; Blanchard, Patrick; Kiziltas, Alper; Joseph, Paul; Naebe, Minoo
Abstract: Glass fiber‐polyamide 6 (PA6) composites are widely used for various automotive applications, yet the ability to exhibit multifunctional properties and the cost of it remains challenging. Herein this work introduces a cost‐effective approach for utilization of waste glass fiber (GF), green aluminium metal organic framework (Al‐MOF), and industry‐grade graphene nanoplatelets (GNPs) for the fabrication of multifunctional PA6 thermoplastic composites with enhanced mechanical performance and fire retardancy. The results demonstrate that hybrid filler of Al‐MOF and GNPs have a synergistic effect in improving the mechanical properties and fire retardancy of GF reinforced PA6 composites. Compared to the neat PA6, the PA6 composite containing 20 wt% GFs, 5 wt% GNPs, and 5 wt% Al‐MOF exhibited 97% and 93% improvements in tensile and flexural strength, respectively. Also, compared to the neat PA6, 27 and 55°C increases were observed in glass transition temperature ( T g ) and heat deflection temperature, respectively. Thermal stability and fire retardancy of the GFs/PA6 composites were significantly improved when hybridized with GNPs and Al‐MOF. Abstract : A low cost and high‐performancethermoplastic composite for automotive applications was developed. Polyamide 6 compositeswere fabricated using waste glass fibre, water based aluminium metal organicframework, and industry‐grade graphene nanoplatelets. The multifunctionalcomposites showed high mechanical performance and fire retardancy. Improvedtensile and flexural strength alongside higher glass transition temperature andheat deflection temperature was achieved. A synergistic effect between aluminiummetal organic framework and industry‐grade graphenenanoplatelets was identified in improvement of properties.